Animation Film in Writing Teaching Instruction on Narrative Text: Working or not Working? - Ammade, Salasiah; Ziska, Ika Yanti (Universitas Negeri Semarang, 2021)
The teaching writing is still in need of interesting teaching media to support its pedagogy as teaching writing is associated with difficult subject to be taught. Prior researches have been conducted on teaching writing area and the result suggested conducting more study on teaching writing effectively. This study attempts to fulfill the gap and takes teaching media as the focus of the research. This article investigated the employment of animated films as a teaching medium in the teaching of narrative writing tests, as well as if they are still effective in supporting the learning process. The sample of the research was taken from the students of a Junior high school in Parepare, Indonesia which was chosen purposively. Online Google Forms was employed as research tools for the study, and the questionnaire and test writing were used to collect data. Quantitative analysis was used in analyzing the data gathered. Regarding the research result, the data revealed that there is difference result between before and after the research. Students respond positively to an animation video utilized in the study as an alternate media in teaching narrative text of writing. They enjoyed the learning process of writing narrative text via animation film as the media as well as improved their positive energy in writing. It can be suggested for the next researcher to study more in another issue of animation film for teaching.